Platelet rich plasma hydrogels promote in vitro and in vivo angiogenic potential of adipose-derived stem cells. (15th March 2019) - Samberg, Meghan; Stone, Randolph; Natesan, Shanmugasundaram; Kowalczewski, Andrew; Becerra, Sandra; Wrice, Nicole; Cap, Andrew; Christy, Robert
Graphical abstract: Abstract: Despite great advances in skin wound care utilizing grafting techniques, the resulting severe scarring, deformity and ineffective vascularization remains a challenge. Alternatively, tissue engineering of new skin using patient-derived stem cells and scaffolding materials promises to greatly increase the functional and aesthetic outcome of skin wound healing. This work focused on the optimization of a polyethylene glycol modified (PEGylated) platelet-rich plasma (PRP) hydrogel for the protracted release of cytokines, growth factors, and signaling molecules and also the delivery of a provisional physical framework for stem cell angiogenesis. Freshly collected whole blood was utilized to synthesize PEGylated PRP hydrogels containing platelet concentrations ranging from 0 to 200, 000 platelets/µl. Hydrogels were characterized using thromboelastography and impedance aggregometry for platelet function and were visualized using scanning electron microscopy. To assess the effects of PEGylated PRP hydrogels on cells, PRP solutions were seeded with human adipose-derived stem cells (ASCs) prior to gelation. Following 14 days of incubation in vitro, increased platelet concentrations resulted in higher ASC proliferation and vascular gene and protein expression (assessed via RT-PCR, ELISA, and immunochemistry). Using a rat skin excision model, wounds treated with PRP + ASC hydrogels increased the number of vessels in the wound by day 8 (80.2 vs. 62.6 vessels/mm 2 ) compared to controls. In conclusion, the proposed PEGylated PRP hydrogel promoted both in vitro and transient in vivo angiogenesis of ASCs for improved wound healing. Statement of Significance: Our findings support an innovative means of cellular therapy intervention to improve surgical wound healing in a normal wound model. ASCs seeded within PEGylated PRP could be an efficacious and completely autologous therapy for treating patients who have poorly healing wounds caused by vascular insufficiency, previous irradiation, or full-thickness burns. Because wound healing is a dynamic and complex process, the application of more than one growth factor with ASCs demonstrates an advantageous way of improving healing.